Perjalanan Menuju Jiwa Sehat dalam Psikospiritual Ibn 'Arabi - Amalia, Novi Husnatul; Soleh, Achmad Khudori (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Mental health has become a crucial issue in the pressure-laden realities of modern life. The Sufi thought of Ibn Arabi offers an alternative approach that integrates spiritual and psychological dimensions in shaping a healthy soul. This article aims to describe the stages of inner transformation within Ibn Arabi’s psychospiritual framework ranging from the purification of the soul (tazkiyah al-nafs), existential awareness (ma‘rifat), the balance between effort and surrender (ikhtiar-tawakal), to the attainment of self-perfection (insān al-kāmil). This study employs a qualitative method using a library research approach to analyze Ibn Arabi’s primary works and relevant secondary literature. The findings reveal that, according to Ibn Arabi, mental well-being is achieved through a deep and systematic spiritual journey involving emotional regulation, self-acceptance, and the integration of rational, emotional, and spiritual faculties. The peak of this journey is the realization of insān al-kāmil, an individual who is both psychologically and spiritually mature. This article contributes to formulating a holistic mental health model grounded in Sufism, which can serve as a reference for developing transpersonal and Islamic psychotherapeutic approaches.